1990
DOI: 10.1083/jcb.111.4.1571
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic transport of ribosomal subunits microinjected into the Xenopus laevis oocyte nucleus: a generalized, facilitated process.

Abstract: Abstract. To study the biochemistry of ribonucleoprotein export from the nucleus, we characterized an in vivo assay in which the cytoplasmic appearance of radiolabeled ribosomal subunits was monitored after their microinjection into Xenopus oocyte nuclei. Denaturing gel electrophoresis and sucrose density gradient sedimentation demonstrated that injected subunits were transported intact. Consistent with the usual subcellular distribution of ribosomes, transport was unidirectional, as subunits injected into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(69 citation statements)
references
References 58 publications
1
68
0
Order By: Relevance
“…In addition, the partitioning of BRlN219A between the cytoplasm and nuclei of Xanthi protoplasts, combined with the absence of NLSs in this C-terminal region of BRl and our previous studies (Sanderfoot and Lazarowitz, 1995), argues that shuttling of BRl may be essential for its proper function as well. Nuclear shuttle proteins are important components of intercompartmental communication in all eukaryotic cells and have historically been identified based on their nuclear redistribution in heterokaryons or microinjection studies (Bataille et al, 1990;Guichon-Mantel et al, 1994). The only other reported virus-encoded nuclear shuttle protein, the matrix protein M1 of influenza A virus, was deduced based on immunogold localization of M1 to the cytoplasm and nucleus at different times following infection of animal cells (Martin and Helenius, 1991b).…”
Section: Bri Mutants Exhibit Defects In Timing and Subcellular Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the partitioning of BRlN219A between the cytoplasm and nuclei of Xanthi protoplasts, combined with the absence of NLSs in this C-terminal region of BRl and our previous studies (Sanderfoot and Lazarowitz, 1995), argues that shuttling of BRl may be essential for its proper function as well. Nuclear shuttle proteins are important components of intercompartmental communication in all eukaryotic cells and have historically been identified based on their nuclear redistribution in heterokaryons or microinjection studies (Bataille et al, 1990;Guichon-Mantel et al, 1994). The only other reported virus-encoded nuclear shuttle protein, the matrix protein M1 of influenza A virus, was deduced based on immunogold localization of M1 to the cytoplasm and nucleus at different times following infection of animal cells (Martin and Helenius, 1991b).…”
Section: Bri Mutants Exhibit Defects In Timing and Subcellular Targetingmentioning
confidence: 99%
“…Such proteins include the major nucleolar proteins nucleolin and No38 (Borer et al, 1989;Laskey and Dingwall, 1993;SchmidtZachmann et al, 1993), members of the 70-kD family of heat-shock proteins (Mande1 and Feldherr, 1990), the heterogeneous nuclear RNA-packaging protein A1 (Pinol-Roma and Dreyfuss, 1992), splicing factor UlA (Kambach and Mattaj, 1992), the nucleolar protein Noppl40 (Meier and Blobel, 1992), the progesterone receptor (Guichon-Mantel et al, 1991), and the influenza M1 matrix protein (Martin and Helenius, 1991b). Because the rate of nuclear import far exceeds that of nuclear export, these proteins characteristically accumulate in nuclei, and shuttling is usually demonstrated by the redistribution of nuclear proteins in heterokaryons or in microinjection studies (Bataille et al, 1990;Schmidt-Zachmann et al, 1993;Guichon-Mantel et al, 1994). Studies demonstrate that masking of nuclear retention signals, as well as the presente of an intact NLS, is required for a karyophilic protein to exit to the cytoplasm and thus function as a shuttle protein, and they have further suggested that most nuclearlocalized proteins may in fact potentially be shuttle proteins (Schmidt-Zachmann et al, 1993;Guichon-Mantel et al, 1994).…”
mentioning
confidence: 99%
“…Newly synthesized ribosomal proteins are imported into the nucleus and subsequently accumulate in the nucleoli at the site of ribosome biogenesis (Lastick, 1980;Sommerville, 1986;Warner, 1990). Assembled ribosomal subunits are exported through the nuclear pores into the cytoplasm (Khanna-Gupta and Ware, 1989;Bataille et al, 1990) in which they become engaged in protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…mRNA export is facilitated by its 5' m7G cap (10, 11). Exit of tRNAs and ribosomal subunits appears to be receptor mediated (9,12).…”
Section: Introductionmentioning
confidence: 99%
“…mRNA export is facilitated by its 5' m7G cap (10, 11). Exit of tRNAs and ribosomal subunits appears to be receptor mediated (9,12).Because colloidal gold coated with poly(A), tRNA, or 5S RNA microinjected into the nucleus exits via nuclear pores (13) and because exit of tRNA and 5S RNA is inhibited by antibodies that react with pore complexes (14), it is likely that mRNA also exits via pores. Maximal mRNA release from isolated animal cell nuclei requires ATP (15-17).…”
mentioning
confidence: 99%